Features of growing a sunflower of foreign selection in conditions of Luhansk region - Маслійов, С. В.; Степанов, В. В.; Ярчук, І. І. (Scientific Progress & Innovations, 2018)
The characteristics of foreign sunflower hybrids, which are most common in the Steppe zone of Ukraine, are given. A search for the most productive sunflower hybrids for growing in Luhansk region, which are highly adaptable to the conditions of insufficient moistening and large contamination of the fields by a sunflower broomrape, has been conducted. A broomrape is a parasitic plant, up to 65 cm high, which forms 500 thousand seeds having the ability to persist in the soil up to 20 years. The broomrape parasitizes on the roots of a sunflower and rapidly inhibits the growth and development, as a result of which the yield of the sunflower falls significantly. Among domestic hybrids, the majority is resistant to 4–5 races A-E, while foreign sunflower hybrids have a resistance to 7 races of A-G. The best technology of growing of foreign sunflower hybrids to obtain a high yield is described. In conditions of Luhansk region the best sunflower precursors are winter crops, corn, legumes, barley. In our case, winter wheat was a precursor of the sunflower. Recommendations for the soil treatment, application of mineral fertilizers, sowing time, seeding rates, crop care were provided. Since autumn, plowing to a depth of 25–27 cm was carried out. In the spring, in order to close the humidity by plowing, an alignment of the plowland was carried out. Due to the weak clogging with weeds, one pre-sowing cultivation was carried out to a depth of 5–6 cm. Strawberry herbicide Kratos was introduced directly before cultivation against the germs of weed vegetation. The main measures for the crop care and weed control are also described. Pre-emergence harrowing across the crops was conducted. In sunflower crops, 1–2 inter-row treatments with a ridger can be carried out to put the weeds in rows. One treatment was performed. Hybrids, which help to reduce the yield from new races and are resistant to: phomopsis, white rot of composite flowers, white rot of stems and unreal downy mildew, are shown. A perspective list of foreign hybrids that can produce a high sunflower yield under the same conditions of cultivation is provided. The best indicators for yield of tested hybrids by species with a humidity index of less than 8.0 % are Pioneer: P64LC108 with a yield of 27.75 c/ha, P63LE113 – 27.25 c/ha and PR64F66 – 25.00 c/ha. The best yields from the hybrids of the firm Limagrain were: LH5662 – 24.00 c/ha and LH50635 – 23.00 c/ha. Among the hybrids of Syngenta seeds the best result was shown by SI Arizona yield of 23.50 c/ha with 7.6 % moisture content.